Psychometric properties of the Child and Adolescent PsychProfiler v5: a measure for screening 14 of the most common DSM-5 disorders - Langsford, Shane; Gomez, Rapson; Houghton, Stephen; Karimi, Leila (Frontiers in Psychology, 2024)
Introduction The Child and Adolescent PsychProfiler version 5 (CAPP v5, 2014) is a measure for screening 14 common DSM-5 disorders in children and adolescents. The separation of Attention-Deficit/Hyperactivity Disorder (ADHD) and Specific Learning Disorder (SLD) by subtype results in 17 screening scales covering the 14 disorders. Theoretically then, the CAPP v5 should have a 17-factor structure, however, to date no published study has confirmed this. Additionally, there has been no comprehensive evaluation of the reliability and validity of the screening scales in this measure. These were examined across two different studies. Study 1 examined support for the 17-factor model of the parent-report version of the CAPP (CAPP-PRF) in a large group of adolescents from the general community. It also examined the internal consistency reliability and discriminant validity of the factors in this measure. Study 2 examined the validity of these factors in a clinic-referred group of adolescents. Methods In Study 1, 951 parents completed the CAPP-PRF on behalf of their adolescents [mean (standard deviation) = 14.54 years (1.66 years)]. In Study 2, 173 parents completed the CAPP-PRF on behalf of their clinic-referred adolescent children [mean (standard deviation) = 14.5 years (1.84 years)]. Adolescents also completed a number of measures and tests for the purpose of assessing their behavior, IQ, and academic abilities. Results The results in Study 1 supported a 17-factor model, and virtually all of the factors in this model showed acceptable reliability (alpha and omega coefficients), and discriminant validity. Study 2 demonstrated good support for the validity of the scales in the CAPP-PRF. Discussion These findings indicate acceptable psychometric properties for the CAPP-PRF, and its utility for screening the more common DSM-5 disorders in children and adolescents.